Estimating mean change in population salt intake using spot urine samples - Petersen, K; Wu, J; Webster, J; Grimes, C; Woodward, M; Nowson, C; Neal, B (Oxford University Press, 2016)
Background Spot urine samples are easier to collect than 24-hour urine samples and can be used with estimating equations to derive the mean daily salt intake of a population. Whether equations using data from spot urine samples can also be usedto estimate change in mean daily population salt intake over time is unknown. To compare estimates of change in mean daily population salt intake based upon 24-hour urine collections with estimates derived using equations based on spot urine samples. Methods aired and unpaired 24-hour urine samples and spot urine samples were collected from individuals in two Australian populations in 2011 and 2014. Estimates of change in daily mean population salt intake between 2011 and 2014 were obtained directly from the 24-hour urine samples and by applying established estimating equations (Kawasaki, Tanaka, Mage, Toft, INTERSALT) to the data from spot urine samples. Differences between 2011 and 2014 were calculated using mixed models. Results A total of 1000 participants provided a 24-hour urine sample and spot urine sample in 2011 and 1012 did so in 2014 (paired samples n=870; unpaired samples n=1142). The mean (95% confidence interval) difference in population salt intake between 2011 and 2014 determined from the 24-hour urine samples was 0.48g/day (-0.74 to -0.21; p<0.001). The corresponding result estimated from the spot urine samples were -0.24 g/day (-0.42 to -0.06; p=0.01) using the Tanaka equation, -0.42 g/day (-0.71 to -0.12; p=0.005) using the Kawasaki equation, -0.51 g/day (-1.00 to -0.01; p=0.046) using the Mage equation, -0.26 g/day (-0.42 to -0.10; p=0.001) using the Toft equation, -0.20g/day (-0.32 to -0.09; p=0.001) using the INTERSALT equation and -0.27g/day (-0.39 to -0.15; p<0.001) using the INTERSALT equation with potassium. The differences derived from the 24-hour collections and estimating equations were not different (all p>0.058). Conclusions All the estimating equations based upon spot urine samples identified a similar difference in daily salt intake to that detected bythe 24-hour urine samples. These data suggest that methods based upon spot urine samples are likely toprovide an approach to measuring change in mean population salt intake.